(untitled) (Libellarium: journal for research in the field of information and related sciences, 2022)
Aim. The paper describes a problem-based learning assignment through which conservation-restoration students become acquainted with the assessment and management of risks to cultural heritage. The assignment includes identification of threats, writing incident scenarios, proposing mitigation measures and identifying persons/institutions that can implement them. All risks are considered in the assignment, not just those related to disasters. Approach/methodology. In the Introduction section, the concept of risk assessment and the context of the assignment are explained. A short description of objects selected as case studies is provided (three sculptures from the Sisak Steelworks Sculpture Park), as well as basic information about the students who worked on the assignment. Next, all the steps of the assignment are described. The final results are only broadly indicated. Findings. Seventy-eight different incident scenarios were identified for outdoor sculptures. To help the reader understand the idea behind the assignment, mitigation measures for three incident scenarios are presented, and potential stakeholders listed. Practical implications. Although the assignment used outdoor sculptures as case studies, it can be applied to any object or collection. The assignment does not have to be included in a preventive conservation course, nor does it have to be directed only to (conservation-restoration) students: it can be used by museum and heritage professionals as a first step in risk assessment for collections. Originality/value. The topic presented in this paper is not well represented in Croatian professional literature. The assignment may be considered innovative in the context of the methodology of teaching conservation-restoration at higher education institutions in Croatia.